2022
DOI: 10.1007/s12035-022-02941-0
|View full text |Cite
|
Sign up to set email alerts
|

Long Intergenic Noncoding RNAs Affect Biological Pathways Underlying Autoimmune and Neurodegenerative Disorders

Abstract: Long intergenic noncoding RNAs (lincRNAs) are a class of independently transcribed molecules longer than 200 nucleotides that do not overlap known protein-coding genes. LincRNAs have diverse roles in gene expression and participate in a spectrum of biological processes. Dysregulation of lincRNA expression can abrogate cellular homeostasis, cell differentiation, and development and can also deregulate the immune and nervous systems. A growing body of literature indicates their important and multifaceted roles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 159 publications
0
3
0
Order By: Relevance
“…MEG8 is a member of a lncRNA cluster, including MEG3 and MEG9 , involved in the response to glycine stimulation in a N-methyl-d-aspartate glutamate receptors (NMDAR)-dependent manner in a murine model ( Tan et al, 2017 ) and this is relevant because the NMDA signaling is impaired in AD ( Dore et al, 2017 ). MEG9 has been recently reported to be downregulated in AD hippocampus ( Wang et al, 2022 ) and involved in the pathogenesis of autoimmune and neurodegenerative diseases ( Plewka and Raczynska, 2022 ). Regarding PCA3 , it was extensively studied in cancer ( Lemos et al, 2019 ) and was found to be differentially expressed in the exosomes of cerebrospinal fluid of AD patients ( Gui et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…MEG8 is a member of a lncRNA cluster, including MEG3 and MEG9 , involved in the response to glycine stimulation in a N-methyl-d-aspartate glutamate receptors (NMDAR)-dependent manner in a murine model ( Tan et al, 2017 ) and this is relevant because the NMDA signaling is impaired in AD ( Dore et al, 2017 ). MEG9 has been recently reported to be downregulated in AD hippocampus ( Wang et al, 2022 ) and involved in the pathogenesis of autoimmune and neurodegenerative diseases ( Plewka and Raczynska, 2022 ). Regarding PCA3 , it was extensively studied in cancer ( Lemos et al, 2019 ) and was found to be differentially expressed in the exosomes of cerebrospinal fluid of AD patients ( Gui et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…An aberrant expression of HERVs associates with chronic inflammatory or degenerative diseases of the nervous system, such as multiple sclerosis, amyotrophic lateral sclerosis (ALS), or schizophrenia as well as with cancer progression 46,47 . Likewise, mutations of lincRNAs or their deregulation have been linked to tumorigenesis and genetically inherited diseases 18,28,48 . Unfortunately, U7-dependent lincRNAs and HERV1/LTR12s are poorly studied, and their function remains a mystery.…”
Section: Disscussion U7 Snrna Acts As a Transcription Inhibitor To Pr...mentioning
confidence: 99%
“…It is known that lincRNAs affect biological pathways in autoimmune and neurodegenerative disorders [ 10 ], cardiovascular diseases [ 9 ], inflammation [ 11 , 12 ], and normal and malignant hematopoiesis [ 13 ]. LincRNAs are aberrantly expressed in various malignant tumors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%